Shame! Self-stigmatisation as an obstacle to sick doctors returning to work: a qualitative study. Issue 5 (15th October 2012) - Henderson, Max; Brooks, Samantha K; del Busso, Lilliana; Chalder, Trudie; Harvey, Samuel B; Hotopf, Matthew; Madan, Ira; Hatch, Stephani
Abstract : Objective: To explore the views of sick doctors on the obstacles preventing them returning to work. Design: Qualitative study. Setting: Single participating centre recruiting doctors from all over the UK. Participants: Doctors who had been away from work for at least 6 months with physical or mental health problems, drug or alcohol problems, General Medical Council involvement or any combination of these, were eligible. Eligible doctors were recruited in conjunction with the Royal Medical Benevolent Fund, the General Medical Council and the Practitioner Health Programme. These organisations approached 77 doctors; 19 participated. Each doctor completed an in-depth semistructured interview. We used a constant comparison method to identify and agree on the coding of the data and the identification of a number of central themes. Results: The doctors described that being away from work left them isolated and sad. Many experienced negative reactions from their family and some deliberately concealed their problems. Doctors described a lack of support from colleagues and feared a negative response when returning to work. Self-stigmatisation was central to the participants' accounts; several described themselves as failures and appeared to have internalised the negative views of others. Conclusions: Self-stigmatising views, which possibly emerge from the belief that 'doctors are invincible', represent a major obstacle to doctors returning to work. From medical school onwards cultural change is necessary to allow doctors to recognise their vulnerabilities so they can more easily generate strategies to manage if they become unwell.